1069. Predictive Factors for Metastatic Infection in Patients With Bacteremia Caused by Staphylococcus aureus. (26th November 2018) - Shimizu, Akihiro; Horino, Tetsuya; Hosaka, Yumiko; Hoshina, Tokio; Nakaharai, Kazuhiko; Lee, Kwangyeol; Miyajima, Makiko; Nakazawa, Yasushi; Yoshida, Masaki; Yoshida, Hiroshi; Hori, Seiji
Abstract: Background: Metastatic infections, such as infective endocarditis and pyogenic spondylitis, are very serious complications of Staphylococcus aureus bacteremia (SAB), because failure to identify metastatic infections may cause poor prognosis. The aim of the present study is to determine the predictive factors for metastatic infections of SAB. Methods: This retrospective cohort study was conducted among patients with bacteremia due to S. aureus (including both methicillin-sensitive S. aureus and methicillin-resistant S. aureus : MSSA and MRSA) in The Jikei University Kashiwa Hospital. The study population comprised 125 adult patients with SAB between January 2014 and December 2017. Patients, that died or transferred within 3 months after the initial positive blood culture, were excluded, because metastatic infection was defined as deep-seated infection detected within 3 months after the initial positive blood culture. We analyzed several factors, including demographics, comorbidities, community acquisition, primary site of infection, persistent fever and laboratory data such as c-reactive protein (CRP) levels after treatment. Results: Seventy-four patients met inclusion criteria of this study. The most common primary site of bacteremia was catheter-related [24 (32.4%) of 74]. Metastatic infection occurred in 22 (29.7%) of 74 patients, and spondylitis was most common, following psoas abscess. Of these, 11 infections (50% of 22) were community acquired. We did not find any significant differences in demographics and comorbidities, except central venous catheter-associated bloodstream infection, which was associated with low rate of metastatic infection. By multivariate analysis, the predictive factors associated with the development of metastatic infection were community onset of infection (OR 11.6; 95% CI 2.98–45.1; P < 0.001), persistent fever over 72 hours (OR 6.7; 95% CI 2.12–21.8; P = 0.001), and higher CRP levels (>3 mg/dL) lasting 2 weeks after the administration of appropriate antibiotics (OR 7.47; 95% CI 2.39–23.3; P < 0.001). Conclusion: This study demonstrated that additional diagnostic tests to identify metastatic infection should be performed, especially in the patients with community-acquired SAB, persistent fever or persistently high CRP levels after the administration of appropriate antibiotics. Disclosures: All authors: No reported disclosures.